1989
DOI: 10.2307/2409379
|View full text |Cite
|
Sign up to set email alerts
|

Safety Factors in Vertical Stems: Evidence from Equisetum hyemale

Abstract: Predictions from a mechanical model for hollow vertical stems are tested against morphometric and mechanical studies of the vertical stems of Equisetum hyemale. The model predicts 1) that the wall thickness of hollow internodes must be at least 15% of the external radius of shoots, 2) that the elastic modulus of stems is quantitatively related to the ratio of apoplast (cell walls) to symplast (cytoplasm) areas in transverse sections through stems, and that (3) hollow stems are designed to sustain an additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The trends in the safety factors with height are in agreement with whole-tree safety factors for mechanical failure under realistic loading conditions (mattheck et al 1993). The safety factor for mechanical instability has been shown to decrease with tree height and several studies have reported trunk safety factors for mechanical instability of about 4 (niklas 1989;domec & Gartner 2002b;Peltola 2006), similar to the values reported here for the safety factor for tracheid implosion. These published values as well as our values for tracheid implosion suggest that trees are mechanically overbuilt.…”
Section: Trunk Segmentation In Relation To Safety Factors: Trends Witsupporting
confidence: 86%
“…The trends in the safety factors with height are in agreement with whole-tree safety factors for mechanical failure under realistic loading conditions (mattheck et al 1993). The safety factor for mechanical instability has been shown to decrease with tree height and several studies have reported trunk safety factors for mechanical instability of about 4 (niklas 1989;domec & Gartner 2002b;Peltola 2006), similar to the values reported here for the safety factor for tracheid implosion. These published values as well as our values for tracheid implosion suggest that trees are mechanically overbuilt.…”
Section: Trunk Segmentation In Relation To Safety Factors: Trends Witsupporting
confidence: 86%
“…The very specialized genus has been of research interest for decades (e.g. Tschudy 1939 ; Bierhorst 1958 ; Niklas 1989 , 1997 ; Spatz et al 1998 ), the “scouring rushes” (Equisetaceae) also because of their abnormal high accumulation of silica of up to 25% of dry weight (Timell 1964 ). In spite of the prominence of silicon as a mineral constituent of all terrestrial plants from 1% to several percent of the dry fraction, it is not counted among the elements defined as “essential”, except for members of the Equisetaceae (Epstein 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, anatomy, as well as morphometric stem structure parameters, which are variable depending on the stem height, tends toward an increase in mechanical stability. The horsetail is a primitive plant and is not capable of dynamic mechanical adaptation via the formation of specialized tissues typical of specific biomechanical conditions (e.g., reaction wood), of which the higher plants are capable, but its reaction consists in an allometric change of the proportions of individual body parts (Niklas 1989c ).…”
Section: Introductionmentioning
confidence: 99%